Wrist Proprioception: Amplitude or Position Coding? - Marini, Francesca; Squeri, Valentina; Morasso, Pietro; Masia, Lorenzo (Frontiers in Neurorobotics, 2016)
This work examines physiological mechanisms underlying the position sense of the wrist, namely the codification of proprioceptive information related to pointing movements of the wrist towards kinesthetic targets. Twenty-four healthy subjects participated to a robot-aided assessment of their wrist proprioceptive acuity to investigate if the sensorimotor transformation involved in matching targets located by proprioceptive receptors relies on amplitude or positional cues. A joint position matching test was performed in order to explore such dichotomy. In this test, the wrist of a blindfolded participant is passively moved by a robotic device to a preset target position and, after a removal movement from this position, the participant has to actively replicate and match it as accurately as possible. The test involved two separate conditions: in the first the matching movements started from the same initial location; in the second one the initial location was randomly assigned. Target matching accuracy, precision and bias in the two conditions were then compared. Overall results showed a consistent higher performance in the former condition than in the latter, thus supporting the hypothesis that the joint position sense is based on vectorial or amplitude coding rather than positional.